Change in Mass of Spinning Black Holes Due to Change in Angular Momentum for Max. Spin - Mahto, Dipo; Kumari, Anuradha (New Insights into Physical Science Vol. 12, 2021)
The present chapter gives a model for the change in mass of spinning black holes w.r.t. the angular momentum in XRBs & AGN for maximum spin and concludes that the change in mass of the spinning black holes due to corresponding change in the angular momentum for maximum spinning rate of black holes (a*=1) decreases with increasing mass of the black holes.